Implikasi Yuridis Perkawinan Campuran Terhadap Pewarisan Tanah Bagi Anak - Putu Devi Yustisia Utami (Fakultas Hukum, Universitas Warmadewa, 2021)
Indonesian citizens and foreigner who carry out marriages in Indonesia can face any problems regarding the personal status of the child and the inheritance system of the land rights, by considering both of their parents are subject to different legal jurisdictions. This study aims to determine the juridical implications of mixed marriages on the citizenship of the children and the inheritance system of the land rights. Normative legal research is used in this paper. The conclusions are, first, the juridical implications of mixed marriages to the citizenship of the children are the children has limited dual citizenship, second, according with Agrarian Law, children who have dual citizenship can only inherit land use rights and can’t inherit ownership rights, bussiness use right and building right.